Acute unintentional poisoning with isopropyl alcohol in the Pereira Rossell Pediatric Emergency WardAcute unintentional poisoning with isopropyl alcohol in the Pereira Rossell Pediatric Emergency Ward: Three clinical cases (Archives of Pediatrics of Uruguay, 2020)
Acute poisoning in pediatric emergency services is an important part of the emergency pediatric pathology due to its potential risk. CIAT receives an average of 10,000 consultations annually, 45% of which are from children. Acute isopropanol poisoning is rare but potentially serious. CIAT has recorded 34 cases in the last 5 years. Isopropyl alcohol is found in many cleaning products and disinfectants. Acute poisoning is initially characterized by digestive symptoms. Some neurological manifestations may arise during the acute poisoning evolution, such as, depression of consciousness, hypotonia and hyporeflexia, associated with hypoglycemia, elevated osmolar gap, ketonemia and ketoneuria. In severe cases, it can cause hypothermia, hypotension and arrhythmia. Metabolic acidosis is rare, unlike what happens with other alcohols. In this case, acute toxicity largely depends on the formation of metabolites; in this case, isopropanol and acetone are responsible for clinical manifestations and alterations in laboratory studies. We hereby present three clinical cases of children aged 96, 18 and 15 months. The three cases evolved favorably in 72-96 hours and, as described in the literature, the prognosis in general is good and without sequelae. The approach to these patients in the emergency ward was the pediatric evaluation triangle and the A, B, C, D, E sequence in order to identify early the need to perform metabolic corrections and / or support functions.
Keywords: 2-Propanol; Poisoning; Pediatrics